Whistleblowing over patient safety and care quality: a review of the literature. Issue 6 (5th September 2019) - Blenkinsopp, John; Snowden, Nick; Mannion, Russell; Powell, Martin; Davies, Huw; Millar, Ross; McHale, Jean
Abstract : Purpose: The purpose of this paper is to review existing research on whistleblowing in healthcare in order to develop an evidence base for policy and research. Design/methodology/approach: A narrative review, based on systematic literature protocols developed within the management field. Findings: The authors identify valuable insights on the factors that influence healthcare whistleblowing, and how organizations respond, but also substantial gaps in the coverage of the literature, which is overly focused on nursing, has been largely carried out in the UK and Australia, and concentrates on the earlier stages of the whistleblowing process. Research limitations/implications: The review identifies gaps in the literature on whistleblowing in healthcare, but also draws attention to an unhelpful lack of connection with the much larger mainstream literature on whistleblowing. Practical implications: Despite the limitations to the existing literature important implications for practice can be identified, including enhancing employees' sense of security and providing ethics training. Originality/value: This paper provides a platform for future research on whistleblowing in healthcare, at a time when policymakers are increasingly aware of its role in ensuring patient safety and care quality.